Komunikasi Simbolik Dalam Upacara Pernikahan Manjapuik Marapulai di Nagari Paninjauan Sumatera Barat - Lusiana Andriani Lubis; Zikra Khasiah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2016)
The goal is this research to see the symbols of figurative language and to analyze the meaning and significance of symbols figurative language in the wedding ceremony manjapuik marapulai in Paninjauan village, Tanah Datar district, West Sumatera. The research employs qualitative study using content analysis (symbolic) and analysis of Roland Barthes semiology be the significance of the two stages (two orders of signification) denotation and connotation, as well as mythical as the development of connotation. The study found that symbols contained in panitahan at a ceremony manjapuik marapulai conform with values and philosophy of Minang adopted by local community. Symbols are included in the 15 sentences that comes from nature, conform with the philosophy of alam takambang manjadi guru as the sentence Tantangan kato ayam lai barinduak, which is a lesson from nature that chickens need of parent in guiding his life as well as humans who need parents in shows about customs. One sentence that comes to the religious teachings of Islam: Adat badiri di nan patuik, syarak mamakai pado dalil, limbago duduak bajauahan, tarapak sambah ka tangah, taunjuak ka muko rapek, the doctrine greeting to people who attend an event. Then 11 sentences that comes to tradition, philosophy, ideology and ethics of society as a sentence Pusako duduak di nan rapek, kato surang dibulati, kato basamo dipaiyo, direnjeang kato jo mupakat which is the ideology of the people in Paninjauan village that is discussion.